Comparative research of a motor car motion in the case of the loss of contact with the road surface - Lukoševičiene, Ona; Bogdevičius, Marijonas; Nagurnas, Saulius; Pečeliūnas, Robertas (Transport, 2004)
The paper describes the car motion when the contact between its wheels and the road surface is lost. A simulation of such car motion was carried out using a mathematical package “Maple 6” for the two cases:• The car flies off a horizontal surface;The car runs over a springboard.The dependencies of the main parameters of motion (velocity Va and distance S) upon the height H of the horizontal road step or upon the springboard height and its inclination angle (in the second case) a were found. The work presents the graphs of these motion parameters and evaluates the influence of air resistance in both cases.First Published Online: 27 Oct 2010